Perspective of Islamic Law and Ulama Polemics about Women Judges (Gender Analysis and Moderation of Fiqh) - Kholiq, Achmad; Zein, Achyar; Haerany, Anne (Ann Publisher, 2024)
This study aims to investigate and debate the validity of women's opinions founded on the normative Islamic viewpoint known as fiqh. This research endeavor endeavors to scrutinize the arguments of various ulama, or Muslim scholars, concerning female judges while maintaining a foundation in fiqh, the body of Islamic law. This study's technique combines focus group discussions (FGD) and content analysis with qualitative approaches. FGD is held with numerous lecturers and specialists in Islamic law at the Faculty of Sharia and Law at Institut Agama Islam Negeri Syekh Nurjati Cirebon. The study's conclusions, which come from at least three well-known ulama or Muslim scholars, indicate that the debate among fiqh experts on the standing of women judges was affected by several factors.